2007
DOI: 10.1080/02841850701342138
|View full text |Cite
|
Sign up to set email alerts
|

Color-flow Doppler sonography in the differential diagnosis and management of amiodarone-induced thyrotoxicosis

Abstract: CFDS is a useful tool in the differential diagnosis of AIT. This differentiation appeared to be of clinical relevance as regards therapeutic choice. Separate evaluation of parenchymal blood flow from that of nodules may prove beneficial in the diagnosis of underlying thyroid diseases in patients with type 1 AIT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
29
0
7

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 27 publications
3
29
0
7
Order By: Relevance
“…The diagnostic uncertainty surrounding these forms of AIT is well reflected by recent questionnaire-based surveys carried out among expert thyroidologist members of the European Thyroid Association (9), Latin American Thyroid Society (10), and American Thyroid Association (11). In general, measurement of thyroidal radioactive iodine uptake (RAIU) and assessment by color flow Doppler sonography (CFDS) are considered the best tools to differentiate type 1 and type 2 AIT (12)(13)(14). In fact, RAIU usually is very lowto-suppressed in type 2 AIT and low-to-normal in type 1 AIT, while CFDS usually show a pattern 0 (absent vascularity) in type 2 AIT and a pattern I to III (normal-to-increased vascularity) in type 1 AIT.…”
mentioning
confidence: 99%
“…The diagnostic uncertainty surrounding these forms of AIT is well reflected by recent questionnaire-based surveys carried out among expert thyroidologist members of the European Thyroid Association (9), Latin American Thyroid Society (10), and American Thyroid Association (11). In general, measurement of thyroidal radioactive iodine uptake (RAIU) and assessment by color flow Doppler sonography (CFDS) are considered the best tools to differentiate type 1 and type 2 AIT (12)(13)(14). In fact, RAIU usually is very lowto-suppressed in type 2 AIT and low-to-normal in type 1 AIT, while CFDS usually show a pattern 0 (absent vascularity) in type 2 AIT and a pattern I to III (normal-to-increased vascularity) in type 1 AIT.…”
mentioning
confidence: 99%
“…This differentiation appeared to be of clinical relevance regarding therapeutic choice and outcome [94,95]. Separate evaluation of parenchymal blood flow from that of nodules may prove beneficial in the diagnosis of underlying thyroid diseases in patients with type 1 AIT [91].…”
Section: Conventional B-mode Ultrasoundmentioning
confidence: 99%
“…Using a classification that subdivides CDI features into four patterns (0-III), some authors have reported that CDI showed mild to markedly increased flow in the thyroid in patients with AIT type 1, whereas flow within the thyroid is markedly decreased or absent in patients with AIT type 2 [91][92][93]. Moreover, the analysis of nodular and extranodular blood flow was useful in the definition of the underlying thyroid diseases in type 1 AIT, being able to differentiate toxic multinodular goiter and toxic adenoma from Graves' disease [91]. This differentiation appeared to be of clinical relevance regarding therapeutic choice and outcome [94,95].…”
Section: Conventional B-mode Ultrasoundmentioning
confidence: 99%
“…It is reported that CFDS rapidly differentiates type I and type II AIT (5,6,19) (Figs. 1, 2 and 4), we recommend near total or total thyroidectomy for these patients, since hyperthyroidism is immediately controlled and heart failure is gradually resolved.…”
Section: Type II Ait Might Be At Least Partly Involved (Mixed Type)mentioning
confidence: 99%
“…In addition, type I AIT associated with Graves' disease has been reported in only a few patients. Its incidence in type I AIT are 2 of 12 (4), 6 of 16 (5) and 1 of 11 (6) in iodine-deficient countries. In contrast, in an iodinesufficient country like Japan, type I AIT associated with toxic multinodular goiter has not been reported to date (7).…”
Section: Introductionmentioning
confidence: 99%